Low Programmed Cell Death 5 Expression is a Prognostic Factor in Ovarian Cancer - Li Gao; Xue Ye; Rui-Qiong Ma; Hong-Yan Cheng; Hong-Jing Han; Heng Cui; Li-Hui Wei; Xiao-Hong Chang (Chinese Medical Journal, 2015)
Background: Ovarian cancer is a leading gynecological malignancy. We investigated the prognostic value of programmed cell death 5 (PDCD5) in patients with ovarian cancer. Methods: Expression levels of PDCD5 mRNA and protein were examined in six ovarian cancer cell lines (SKOV3, CAOV3, ES2, OV1, 3AO, and HOC1A) and one normal ovarian epithelial cell line (T29) using reverse transcription polymerase chain reaction, Western blotting, and flow cytometry. After inducing PDCD5 induction in SKOV3 cells or treating this cell line with taxol or doxorubicin (either alone or combined), apoptosis was measured by Annexin V-FITC/propidium iodide staining. Correlations between PDCD5 protein expression and pathological features, histological grade, FIGO stage, effective cytoreductive surgery, and serum cancer antigen-125 values were evaluated in patients with ovarian cancer. Results: PDCD5 mRNA and protein expression were downregulated in ovarian cancer cells. Recombinant human PDCD5 increased doxorubicin-induced apoptosis in SKOV3 cells (15.96 ± 2.07%, vs. 3.17 ± 1.45% in controls). In patients with ovarian cancer, PDCD5 expression was inversely correlated with FIGO stage, pathological grade, and patient survival (P < 0.05, R = 0.7139 for survival). Conclusions: PDCD5 expression is negatively correlated with disease progression and stage in ovarian cancer. Therefore, measuring PDCD5 expression may be a good method of determining the prognosis of ovarian cancer patients.